Peran Pembelajaran Aqidah Akhlak dalam Pembinaan Perilaku Siswa Madrasah Tsanawiyah: Studi Kualitatif Pendidikan Agama Islam - Pratista, Hafizha Nazrylya; Amin, Lailla Hidayatul; Mahendra, Viki Bayub (Paedagogie, 2026)
Islamic Religious Education learning, especially the subject of Aqidah Akhlak, has a strategic role in fostering the behavior of students in madrasas. The phenomenon of student delinquency that is still found in the Madrasah Tsanawiyah environment shows the need to strengthen a learning approach that is not only oriented to cognitive aspects, but also to the formation of attitudes and morals. This study aims to analyze the role of Aqidah Akhlak learning in fostering student behavior and identify strategies used by teachers in overcoming student delinquency. This study uses a qualitative approach with a descriptive type of research. Data collection techniques are carried out through interviews, observations, and documentation. The results of the study show that learning Aqidah Akhlak plays a role as a preventive and curative approach in fostering student behavior through teacher examples, habituation of moral values, personal approach, and strengthening faith and moral values in students' daily lives. Learning Aqidah Akhlak not only functions as a transfer of religious knowledge, but also as a means of building sustainable Islamic character. This finding confirms the importance of strengthening the learning of Aqidah Akhlak in Islamic Religious Education as the foundation for fostering the behavior and character of students in madrasas.